Relationship between Adverse Childhood Experiences and Mental Health in Chinese Adolescents: Differences among Girls and Boys - Weiwei Jiang; Mingxia Ji; Xinli Chi; Xiaojiao Sun (Children, 2022)
The negative effects of adverse childhood experiences (ACEs) on individual mental health have been widely demonstrated, yet fewer studies have examined the impact of ACEs on depression and anxiety of Chinese adolescents and their sex differences. This cross-sectional study surveyed 12421 adolescents aged 10–17 in Hechi City, Guangxi Province, to measure their levels of ACEs, depression symptoms, and anxiety symptoms. The results found that: (1) Girls were more likely to experience ACEs than boys (37.67% vs. 32.25%, χ2 = 39.97, p < 0.001). (2) Emotion-related ACEs were more likely to occur among girls, while physical maltreatment, violence, and family dysfunction related ACEs were more likely to occur among boys. (3) Adolescents with ACEs were more likely to develop depression (OR = 4.40) and anxiety symptoms (OR = 4.60) than those without ACEs; adolescents who have encountered “peer isolation” and “emotional neglect” are most likely to develop depression (OR = 6.09/5.04) and anxiety symptoms (OR = 6.14/4.94). (4) The dose-response relationship between the level of ACE exposure and the risk of depression/anxiety symptoms was significant (p < 0.05), i.e., the risk increased as ACE level increased. (5) Girls were more likely to develop depression and anxiety symptoms than boys with the same ACE level. This study deepens the understanding of the prevalence of ACEs, the effect of ACEs on depression and anxiety symptoms, and their sex differences among Chinese adolescents in the underdeveloped regions of China. It provides more empirical support for future work on adolescent mental health protection.